The IMF and Civil Society : Striking A Balance - Dawson, Thomas (IMF Policy Discussion Papers; Policy Discussion Paper, 2001)
In the space of just a few years, the term 'civil society' has entered the international policy vocabulary in many contexts. The IMF's engagement with civil society organizations (CSOs) raises several broad questions: Which CSOs have been, and should be, engaged by the Fund? What questions should IMF-CSO engagement address? What are the limits to the dialogue? This paper examines the evolution of IMF-civil society relations and their effects on the Fund. It also seeks to identify the tensions that underlie the relationship.